2017
DOI: 10.1039/c7sm00097a
|View full text |Cite
|
Sign up to set email alerts
|

Nonspherical armoured bubble vibration

Abstract: In this paper, we study the dynamics of cylindrical armoured bubbles excited by mechanical vibrations. A step by step transition from cylindrical to spherical shape is reported as the intensity of the vibration is increased, leading to a reduction of the bubble surface and a dissemination of the excess particles. We demonstrate through energy balance that nonspherical armoured bubbles constitute a metastable state. The vibration instills the activation energy necessary for the bubble to return to its least ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The results of the current work are valid for quasi-static situations. Experiments report buckling and particle expulsion in highly-dynamic situations in which time-dependent pressure fields change the shape of particle-covered bubbles 1,44 . In these situations both the particle and the fluid inertia are important.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current work are valid for quasi-static situations. Experiments report buckling and particle expulsion in highly-dynamic situations in which time-dependent pressure fields change the shape of particle-covered bubbles 1,44 . In these situations both the particle and the fluid inertia are important.…”
Section: Discussionmentioning
confidence: 99%
“…At small inter-particle separations, the lateral force can be repulsive, and therefore the critical separation distance for particle aggregation on a bubble is significantly decreased by dynamic effects. Dynamic capillary interactions between colloidal particles oscillating at an interface have not yet been observed, likely because of the high surface coverage in typical experiments, resulting in small inter-particle distances such that this theory is not applicable (Poulichet & Garbin 2015; Prabhudesai et al 2017). This work therefore motivates future controlled experiments with sufficiently large inter-particle distances.…”
Section: Discussionmentioning
confidence: 99%
“…Protière et al (2006, 2005) and Moláček & Bush (2013) found that the interactions between drops bouncing on an interface and the capillary waves generated during each impact are responsible for a range of drop dynamics such as inter-drop attraction, repulsion and orbiting. Dynamic capillary interactions could be relevant for the self-assembly of colloids on the interface bubbles and drops deformed by unsteady and dynamic stresses (Mulligan & Rothstein 2011; Poulichet & Garbin 2015; Prabhudesai et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, upon highly dynamic deformation, particle expulsion occurs even for initially cohesive monolayers, because the mechanical energy input to the monolayer is sufficient to re-disperse the particles on the interface [74]. On a larger scale, millimetric particle-coated bubbles with initial anisotropic shapes were found to relax to their equilibrium spherical shape when vibrated, with the excess particles expelled in the surrounding liquid [76].…”
Section: Expulsion Of Interfacial Materialsmentioning
confidence: 99%